Konkurrenssituationen för den skånska grönsaksproduktionen - Lund, Jeanette; Lundgren, Camilla (2007)
The vegetable production in Sweden is concentrated to the very southern parts of the country. This is also were the major wholesalers are located. In recent years, there has been an extreme focus on price on the food market. As there are only a few big wholesalers and also very few food retail chains, these have a great impact on the producers. The pressure from prominent vegetable-producing countries, providing low price products, such as the Netherlands and Spain is strong. During years there has been a development towards fewer but larger and more rational enterprises. The decrease in number of vegetable producers is dramatic and many of the smaller, more local growers are having a hard time staying in the business.